Organizational fans and the mnemonic discourse in the social media: notes based on the study of the Viva Channel - Amaral, Adriana da Rosa; Parada, Augusto Rodrigues (Organicom, 2015)
The perspective addressed in the following discussion presumes the existence of an organizational fan that, due to a uniquebehavior establishes him/herself as a public of interest for the organizations. Starting from this classification and using asa focus of study the Viva Channel, of the Globo Group, one can list what would be the standard of behavior of this new publicand, further, in which way the symbolic exchanges materialize as factors of identification and relationship between the fansand the organizations in digital spaces. Thus, these scenarios point to possible communicational articulations on the partof the organizations for the maintenance of such relationship.